Negara Islam Indonesia Dan Kartosuwiryo (Konsepsi Gerakan Politik, Militer Dan Agama) - miftakhur ridlo (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
Kartosuwiryo was known by many to be the ploclamator of the Indonesian Islamic State, on August 7, 1949 in West Java. Kartosuwiryo has a very complex movement, encompassing political, military and religious conceptions even considered as his Revolutionary path. Kartosuwiryo made Islam a political ideology, according to him, every political struggle must hold to political creed, namely ideology and realistic. The military movement began when Kartosuwiryo formed the Suffah Institute, which became the forerunner of Hezbollah and Sabilillah troopsThe emergence of the Indonesian Islamic State's proclamation movement was the implementation of a Kartosuwiryo thought that contained the concepts of hijrah and jihad. Basically this attitude aims at the foundation of PSII politics, which is sourced from the Qur'an and Sunnah. This attitude includes, among others: First, it contains devotion to God. Second, tell the situation before the migration of the Prophet. Third, narrating the migration of the Prophet from Mecca to Medina. Fourth, the first year of migration. Fifth, the history of Islam from the 2nd century H to the 8th H.